Design of modernized test bench for analysis of cooling systems with intensification under inertial forces field - V. V. Shalay; K. V. Shcherban (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The article discusses the design of a modernized test bench for the study of cooling systems with intensification of inertial forces in the field. This bench will allow investigation the efficiency of heating the hydrocarbon coolant in the field of inertial forces and verification of the calculation results obtained in ANSYS environment